Agricultural change: consequences for southern farms and rural communities - Molnar, Joseph J. ed. (Westview Press ColoradoUS, 1986)
Examines the impact of the rise and fall of new commodities, production technologies and shifting government policies on the lives of generations of farm families in the rural South of the U.S.A.